A comprehensive study on the stability of Desi cotton (Gossypium arboreum) genotypes under rainfed conditions using AMMI and GGE biplot analysis - Sheeba, A; Yogameenakshi, P; Ramakrishnan, S H; Aanandhi, N; Baskar , K (Plant Science Today, 2025)
The present study aims to assess the stable and adaptable cotton genotypes under rainfed vertisol conditions using Additive Main effects Multiplicative Interaction and Genotype and Genotype × Environment (GGE) biplot analyses. Seventeen cotton genotypes were evaluated for seed cotton yield at the Agricultural Research Station, Kovilpatti, over three years (2020, 2021 and 2022), treated as distinct environments. Seed cotton yield was subjected to pooled ANOVA, AMMI and GGE biplot analysis, revealing significant variation between genotypes, environment and GEI, with the climate and G × E interaction accounting for 33.8 % and 27.8 % of the total variation, respectively, in seed cotton yield. Based on AMMI I analysis, the genotypes G5 (TKA 0856) and G13 (TKA 1336) were found to have overall adaptability in all the environments (years) studied and considered stable genotypes. GGE biplot was plotted for seed cotton yield using PC1 and PC2, accounting for 70.2% and 26.2 %, respectively, explaining 96.4 % of the total GEI variance. The winning genotypes identified for three mega-environments are G2 (TKA 0612), G16 (TKA 1104) for the first, G6 (TKA 1035), G13 (TKA 1336) for the second and G11 (TKA 1326), G4 (TKA 0848) for the third respectively. The genotype G6 (TKA 1035) was chosen as the most ideal genotype based on mean vs. stability analysis. Among the test environments, E1 was considered the most discriminating environment suitable for selecting widely adapted genotypes.